The Effectiveness of Using Scaffolding Technique In Teaching Descriptive Text Writing to The Eighth Grade Students of SMP Negeri 3 Onan Ganjang - Simanullang, Lamtiar; Ginting, Fiber Yun Almanda; Pangaribuan, Jontra Jusat (Journal of Applied Linguistics, 2025)
This research was conducted in order to improve students’ writing descriptive text by using scaffolding technique to the eighth zgrade students of SMP Negeri 3 Onan Ganjang. In conducting this research, the writer used Classroom Action Research (CAR). This research showed that teaching writing through Scaffolding Technique to the eighth-grade students of SMP Negeri 3 Onan Ganjang could improve their writing descriptive text. The result of this research showed that the students’ responses after being taught by using Scaffolding Technique are very good. The result of the test showed that the students’ mean score of pre-tests is 46,87 with 4,16% students got score >68, in formative test, the students’ mean score is 63,04 with 41,66% students got score >68, and in post-test, the students’ mean score is 81,75 with 70,83% got score >68. The research findingsscowed that using Scaffolding Technique could improve the students’ writing descriptive text. It is advisable that English teachers could apply Scaffolding Technique in order to improve their students’ writing. Keywords : Scaffolding Technique, Writing, Descriptive Text